Anti-PD-1 antibody therapy for epithelial skin malignancies: An investigator-initiated, open-label, single-arm, multicenter, phase II clinical trial (NMSC-PD1 Study). Issue 44 (30th October 2020) - Ishii, Maki; Hirai, Ikuko; Tanese, Keiji; Fusumae, Takayuki; Nakamura, Yoshio; Fukuda, Keitaro; Uchi, Hiroshi; Kabashima, Kenji; Otsuka, Atsushi; Yokota, Kenji; Yamazaki, Naoya; Namikawa, Kenjiro; et al.
Abstract: Introduction: Malignant cutaneous epithelial tumors comprise various skin malignancies originating from the cutaneous epithelium, including cutaneous squamous cell carcinoma, basal cell carcinoma, and malignant cutaneous adnexal tumors. Treatment options are limited, as the rarity of these tumors, especially among Asians, renders well-controlled clinical trials extremely challenging to conduct. Thus, we designed a clinical trial to evaluate the efficacy and safety of the anti-programmed cell death-1 (PD-1) monoclonal antibody nivolumab in patients with metastatic cutaneous squamous cell carcinomas and other rare metastatic cutaneous epithelial tumors. Methods and analysis: This is an open-label, single-arm, multicenter, phase 2 clinical trial involving patients with metastatic malignant cutaneous epithelial tumors. Nivolumab (480 mg) will be administered intravenously every 4 weeks for a maximum of 26 doses. The primary outcome of the study will be the response rate based on response evaluation criteria in solid tumors, version 1.1. Assuming a null hypothesis of a response rate ⩽5% and an alternative hypothesis of a 25% response rate, a minimum of 26 patients are required to achieve a 5% two-sided type I error and 80% power based on the exact binomial distribution. Finally, a target cohort size of 30 patients was determined as some patient dropout will be expected. Discussion: This is the first phase 2 clinical trial evaluating the efficacy and safety of the PD-1 inhibitor nivolumab in Asian patients with metastatic malignant cutaneous epithelial tumors. The findings of the study will contribute to the development of novel treatment approaches for patients with rare cutaneous malignancies, which remains an unmet clinical need. Trial registration: Registry number: jRCT 2031190048